The progress in understanding and treatment of diabetic retinopathy - Stitt, Alan W.; Hammes, Hans-Peter (Progress in retinal and eye research, 2016)
Diabetic retinopathy is the most frequently occurring complication of diabetes mellitus and remains a leading cause of vision loss globally. Its aetiology and pathology have been extensively studied for half a century, yet there are disappointingly few therapeutic options. Although some new treatments have been introduced for diabetic macular oedema (DMO) (e.g. intravitreal vascular endothelial growth factor inhibitors (‘anti-VEGFs’) and new steroids), up to 50% of patients fail to respond. Furthermore, for people with proliferative diabetic retinopathy (PDR), laser photocoagulation remains a mainstay therapy, even though it is an inherently destructive procedure. This review summarises the clinical features of diabetic retinopathy and its risk factors. It describes details of retinal pathology and how advances in our understanding of pathogenesis have led to identification of new therapeutic targets. We emphasise that although there have been significant advances, there is still a pressing need for a better understanding basic mechanisms enable development of reliable and robust means to identify patients at highest risk, and to intervene effectively before vision loss occurs.
Gesehen am 30.10.2019
Available online 18 August 2015